Health insurance, medical debt, and financial well-being - Benedic N. Ippolito; Michael Batty; Christa Gibbs (American Enterprise Institute (AEI), 2021)
We use credit reports, survey data, and two natural experiments that increase health insurance coverage—Medicare eligibility and the Affordable Care Act's Under 26 provision—to study the financial protection provided by health insurance.
Keywords: A; 330; Affordable Care Act Obamacare; debt; economics; Health Care Policy; Medicare